Systemic approach to causality between poverty and informality in Peru: 2010-2019 - Pérez-Ticse, Juan C. (2022)
Objective. To analyze with a systemic approach, the causality that exists between poverty and informal employment in Peru, considering different factors that affect both variables. Methods. The research is basic, quantitative and explanatory level, we used the 'National Household Survey' (ENAHO), period 2010 to 2019, where we studied the effects of the individual characteristics of household members, sociodemographic, household characteristics, education and employment, performing simultaneous equations calculations with instrumental variables and least squares in two stages. Results. There is a double causality between informal employment and poverty in Peru, since both informality and poverty are found among the less educated, organized and low-skilled sectors, with a higher percentage in rural areas of the country. In addition, small businesses often have very limited access to the market, and therefore tend to offer informal employment. Conclusion. Informal employment and poverty present a bidirectional causal relationship in Peru by 2019.